VD_FINDINFO HC / 2020 / 464 vom 22. Juni 2020 - VD Tribunal cantonal (2020)
ACTION EN CONSTATATION, MEILLEURE FORTUNE, VALEUR LITIGIEUSE, COMPÉTENCE, MAXIME DES DÉBATS | 265a al. 2 LP, 265a al. 4 LP, 326 CPC (CH)